Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles

Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.

Synthesis and assembly of gold nanoparticles in quasi-linear lysine-keggin-ion colloidal particles - Sanyal, A.; Mandal, Sujata; Sastry, M. (Advanced Functional Materials, 2005)
The formation of fiber-like colloidal particles of the amino acid lysine complexed with Keggin ions is demonstrated. The lysine-phosphotungstic acid (PTA) colloidal particles act as excellent templates for the synthesis and assembly of gold nanoparticles wherein the lysine-PTA complex acts as a UV-switchable reducing agent for gold ions. This novel bio-organic-inorganic template shows excellent potential as a regulated nanoreactor for application in programmed nanoparticle synthesis and assembly in a single step.

Synthesis of gold, silver and their alloy nanoparticles using bovine serum albumin as foaming and stabilizing agent - Singh, A. V.; Bandgar, B. M.; Kasture, Manasi; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Materials Chemistry, 2005)
A simple and convenient method for the synthesis of gold, silver and their alloy nanoparticles in a foam matrix using the protein bovine serum albumin (BSA) is reported. BSA is an excellent foaming agent and, by virtue of its zwitterionic character at the protein isoelectric point, may be used to bind to either cationic silver (Ag+) or anionic gold (AuCl4-) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver and gold nanoparticles. The versatility of an amphoteric foaming agent is further demonstrated by the simultaneous binding of Ag+ and AuCl4- ions with zwitterionic BSA leading to the possibility of obtaining Au-Ag alloy nanoparticles in the foam. The BSA molecules coat and stabilize the nanoparticles thus prepared eliminating the necessity of employing an additional stabilizing agent in the experimental recipe.

Synthesis of hydroxyapatite crystals using amino acid-capped gold nanoparticles as a scaffold - Rautaray, D.; Mandal, Sujata; Sastry, M. (Langmuir, 2005)
Inorganic composites are of special interest for biomedical applications such as in dental and bone implants wherein the ability to modulate the morphology and size of the inorganic crystals is important. One interesting possibility to control the size of inorganic crystals is to grow them on nanoparticles. We report here the use of surface-modified gold nanoparticles as templates for the growth of hydroxyapatite crystals. Crystal growth is promoted by a monolayer of aspartic acid bound to the surface of the gold nanoparticles; the carboxylate ions in aspartic acid are excellent hinging sites for Ca2+ ions. Isothermal titration calorimetry studies of Ca2+ ion binding with aspartic acid-capped gold nanoparticles indicates that the process is entropically driven and that screening of the negative charge by the metal ions leads to their aggregation. The aggregates of gold nanopartictes are believed to be responsible for assembly of the platelike hydroxyapatite crystals into quasi-spherical superstructures. Control experiments using uncapped gold nanoparticles and pure aspartic acid indicate that the amino acid bound to the nanogold surface plays a key role in inducing and directing hydroxyapatite crystal growth.